Types of Slang Terms Found in The Movie Dope - Ade Galuh Cahya Dewani; I Gusti Ngurah Parthama (Pusat riset dan Inovasi Nasional, 2025)
This study investigates the types of slang terms found in the movie Dope by classifying them based on their linguistic characteristics and communicative functions. Using Green’s (2002) Slang Theory, the research identifies and categorizes slang into five types: innovative, group-identifying, evasive, reactive, and playful slang. A qualitative descriptive method was applied, with data collected through documentation and analyzed by examining how each slang type is formed and used in context. The findings reveal that innovative slang was the most frequently used, illustrating the dynamic and creative nature of youth language. By focusing on linguistic structure and function rather than cultural context, this study provides insights into how slang operates as a form of informal communication within media. The analysis demonstrates that slang in Dope serves various linguistic purposes such as expressing identity, humor, secrecy, and emotional response, contributing to a broader understanding of informal language use in modern youth discourse.